Paced QRS Duration as the Major Determinant of Pacing Induced Cardiomyopathy in Complete AV Block: Induced Cardiomyopathy in Atrioventricular Block - Khawajakhail, Roomana; Tariq, Hajra; Mansoor, Talia; Aziz, Yasir; Haq, Ijaz Ul; Khan, Shamal; Khan, Khalid Naveed; Sajjad, Waseem (Pakistan Journal of Health Sciences, 2024)
Patients with complete heart block often develop pacing-induced cardiomyopathy (PICM) after placement of a permanent pacemaker. Objective: To establish paced QRS duration as determinant of pacing induced cardiomyopathy in complete Atrioventricular (AV) block. Methods: This descriptive study included 115 male and female patients that had a permanent pacemaker implanted for complete AV block, at the department of Cardiology, Hayatabad Medical Complex, Peshawar, during the period 1st November 2023 till 30th June 2024. Patients were evaluated for the presence of PICM and subsequently grouped as PICM and non-PICM. Paced QRS duration in both groups was compared. Results: PICM was confirmed in 63 patients (54.8%) and 52 (45.2%) were non-PICM. Mean age in PICM group was 71.2 ± 8.7 years and 66.8 ± 9.5 years in non-PICM group. The mean paced QRS duration in PICM group was 200.5 ± 22.3 milliseconds and 168.3 ± 15.7milliseconds in non-PICM group (p value <0.001). Conclusion: Prolonged paced QRS duration was found as key indicator for predicting pacing induced cardiomyopathy in patients with permanent pacing for complete AV block.